NILAI-NILAI ANTI KORUPSI DALAM AJARAN TASAWUF - Mushofa, Mushofa (Universitas Islam Negeri Antasari Banjarmasin, 2022)
Abstract: This paper explains that Sufism is a positive human therapy in dealing with various problems encountered in all aspects of life. Then Sufism is also a way of how humans can be close to their Lord. When the heart is close to God, then by itself, humans will always be close to goodness, good deeds, good attitudes, and behavior. At this point humans can avoid all ugliness, immoral acts, and bad behavior such as corruption. Departing from this, it is important to describe